2021
DOI: 10.5051/jpis.2007540377
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and periodontal disease: a qualitative systematic review of human studies

Abstract: Purpose MicroRNAs (miRNAs) are epigenetic post-transcriptional regulators that modulate gene expression and have been identified as biomarkers for several diseases, including cancer. This study aimed to systematically review the relationship between miRNAs and periodontal disease in humans, and to evaluate the potential of miRNAs as diagnostic and prognostic biomarkers of disease. Methods The review was conducted following the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…As THP-1 monocytes are frequently used to examine innate immune ligand-induced miRNA expression, we observed signifi-cantly increased miR-132 expression with live T. forsythia in this study. The most widely investigated inflammatory miRNA in PD is miR-146a, which was upregulated in 16-week T. forsythia-infected mice as well as overexpressed in saliva of patients with PD [31,100]. It is obvious that the upregulated miRNAs in the current study may also have these functions as it is involved in NF-κB activation for transcription of inflammatory genes.…”
Section: Discussionmentioning
confidence: 76%
“…As THP-1 monocytes are frequently used to examine innate immune ligand-induced miRNA expression, we observed signifi-cantly increased miR-132 expression with live T. forsythia in this study. The most widely investigated inflammatory miRNA in PD is miR-146a, which was upregulated in 16-week T. forsythia-infected mice as well as overexpressed in saliva of patients with PD [31,100]. It is obvious that the upregulated miRNAs in the current study may also have these functions as it is involved in NF-κB activation for transcription of inflammatory genes.…”
Section: Discussionmentioning
confidence: 76%
“…Another study has shown that miR-146a-3p can exert M1 polarization of macrophages by targeting SIRT1 [ 69 ]. A meta-study has found that miR-146a is the most widely researched miRNA in periodontal diseases, and most studies reported higher expression levels of miR-146a in patients with periodontitis than in healthy controls [ 70 ]. miR-146a can also regulate lipid droplet formation by targeting ACSL1, which may be a potential biomarker and therapeutic target for atherosclerosis [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs are defined as molecules without apparent protein-coding potential that regulate complex cellular behaviors, and they are classified into small RNAs such as miRNAs and lncRNAs by length [49] , [50] . Meta-analysis of miRNA expression in periodontitis and peri-implantitis concluded that miRNA-146a and miRNA-142–3p were statistically significant in periodontitis patients [51] , and miRNA-146a is one of the well-analyzed miRNAs in periodontitis [52] . Notably, miR-146a was reported as negatively regulating the innate immune system, and the concentrations were significantly higher in CP patients, and miRNA-146a expression was inversely correlated with TNFα and IL6 expression [53] .…”
Section: Epigenetic Factors Of Periodontitismentioning
confidence: 99%